The influence of Product Quality, Discounts, and Online Customer Reviews on Purchasing Decisions for Jiniso Brand Fashion Products - Putri, Sintya Fitrialin; Subagyo (Universitas Nusantara PGRI Kediri, 2025)
Research objectives: The focus of this study is on the Jiniso fashion brand, specifically looking at how factors like product quality, discounts, and online consumer reviews on the purchasing decisions related to Jiniso fashion brand products, either partially or simultaneously. Design / Method / Approach: This research employs a quantitative methodology utilizing causal techniques. The study's population comprises students from the Faculty of Economics and Business at University Nusantara PGRI Kediri, with a sample consisting of 40 respondents. A non-probability sampling method was applied, specifically a purposeful sampling approach targeting students who had previously purchased products from the Jiniso fashion brand. Data were gathered through an online survey, and the analysis was conducted using multiple linear regression techniques facilitated by IBM SPSS Statistics 27 software. Research findings: Out of the three independent variables studied, online customer reviews (X3) had the most influence on consumers' decisions to buy products from the Jiniso fashion brand, according to the research. The other two variables were discount (X2) and price (X2). On the other hand, there is no evidence that product quality (X1), an independent variable, influences these purchases. Theoretical contribution / Originality: The results of this research could provide a useful reference for future research examining how product quality, promotional discounts, and online customer reviews influence purchasing decisions for Jiniso brand fashion items. Practitioner Implications/ Policy : This research offers general overview in creating of marketing strategies while also clarifying consumer needs and expectations that drive repeat purchases. Research limitations: This research is limitation is on the influence of product quality, discounts, and online customer reviews on the purchasing decisions related to Jiniso Brand fashion products among students. The participants in this research were exclusively drawn from the Faculty of Economics and Business at Nusantara University PGRI Kediri.